Takhrij and Syarah Hadith of Agrotechnology: Preserving The Environment - Nahidl Azka Maulida; Wahyudin Darmalaksana; Liberty Chaidir (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith with regard to agrotechnology. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. The results and discussion of this research is the obligation of every human being to preserve the environment by not cutting trees. The conclusion of this study is the prohibition of illegal cutting of trees and environmental preservation.